Effect of Plant Densities on some Productivity Characteristics of Two Varieties of Arachis hypogaea L. (Sory1 and Sory2) in Syrian Coast. - محمد, يوسف; زينة, ربيع; زليخة, محمد (Latakia University Journal -Biological Sciences Series, 2020)
The research was conducted in Al-Sanobr Agriculture Research Station (Syria/Lattakia) in growing season 2017. The aim of the research is to study the effect of plant densities on some productivity characteristics of Arachis Hypogaea L. Using in research two cultivars of Arachis hypogaea L (sory1 and sory2) and four plant densities (6.66 – 8 – 10 – 13.33 plant.m-2). The Split Plot Design was used in designing this study with three replicates, where the cultivars occupied the main plots while the plant densities occupied split plots. The results indicated that lowest plant density (6.66 plant/m2) had significant increase on all highest plant density (13.33 plant.m-2) in dry weight/plant and weight of 100 seeds (139.16 , 120 g.plant-1 – 46.56 , 44.76 g) respectively, and the lowest plant density (6.66 plant.m-2) had significant increase on all other plant densities (8 – 10 - 13.33 plant.m-2) in number of pods per plant (30.13 , 27.1 , 24.62 , 22.12 pod.plant-1) respectively, as the highest plant density (13.33 plant.m-2) had significant increase on all other plant densities (6.66 – 8 – 10 plant.m-2) in pods yield (2990 , 2542 , 2293 , 2180 kg.ha-1) and seeds yield (2428 , 2084 , 1931 , 1849 kg.ha-1 ) respectively. Where there is no significant deference between the two types in all characteristics except the weight of 100 seed, Sory1 had significant increase on Sory2 (47.24 . 44.11 g) respectively.